(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To find out the frequency and distribution of lymph node metastasis in supraglottic carcinoma. Study Design: Cross sectional study. Methods: 50 cases are included in this study (male-45 and female-5) between the ages of 40- 80 years who were treated from September 2007 to February 2008. Study based on history, clinical, radiological, laboratory and histopathological examination. Results: Highest number of patients was in the age group 50-60 years. Male and female ratio was 9:1. Commonest occupational group was cultivators and most patients come from poor socio-economic class. Smoking was commonest (70%).Out of 50 patients 20 (40%) had their regional lymph node involved. Level-II lymph nodes were involved in higher number of cases. Nodes in advanced stage of involvement were found in most cases. Homolateral involvement of nodes was in most cases (84.21%). Most of the patients present with more than one symptom and the commonest presenting symptoms of supraglottic carcinoma was cough and irritation (90%) followed by dysphagia (76%) and change of voice (72%). Most of the supraglottic growth was exophytic in appearance. The common site involve (50%) in the study were aryepiglottic fold and arytenoids. 80% of patients were present with T2 tumours. Patients were staged according to the TNM feature. Most of the patients (40%) were in stage-III followed by stage-II (24%). Conclusion: Lymphadenopathy is present much higher frequency in supraglottic carcinoma than glottic carcinoma. Key words: Supraglottic Carcinoma; Lymph node DOI: http://dx.doi.org/10.3329/bjo.v17i2.8850 BJO 2011; 17(2): 110-116